2020
DOI: 10.1177/0003134820960063
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Sex Disparities in Trauma Outcomes Based on Geographical Region

Abstract: Objectives Disparities in outcomes among trauma patients have been shown to be associated with race and sex. The purpose of this study was to analyze racial and sex mortality disparities in different regions of the United States, hypothesizing that the risk of mortality among black and Asian trauma patients, compared to white trauma patients, will be similar within all regions in the United States. Methods The Trauma Quality Improvement Program (2010-2016) was queried for adult trauma patients, separating by U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…[25][26][27][28] Previous research has used this approach to evaluate individual state and regional trauma systems. [29][30][31][32][33][34] These observations further align with the work of the Trauma Systems Committee of the American College of Surgeons Committee on Trauma to assess trauma center designation based on population need to ensure timely access to care. 6 As highlighted by the panel, more research is needed to understand the best balance of these priorities (e.g., access, equity, patient volume to care quality relationship) in modern trauma system design.…”
Section: Discussionsupporting
confidence: 53%
“…[25][26][27][28] Previous research has used this approach to evaluate individual state and regional trauma systems. [29][30][31][32][33][34] These observations further align with the work of the Trauma Systems Committee of the American College of Surgeons Committee on Trauma to assess trauma center designation based on population need to ensure timely access to care. 6 As highlighted by the panel, more research is needed to understand the best balance of these priorities (e.g., access, equity, patient volume to care quality relationship) in modern trauma system design.…”
Section: Discussionsupporting
confidence: 53%
“…Further demonstrating a racial disparity found in major cities, the present study found that not only are Black individuals disproportionately affected by MSEs, but also there are more people injured (eTable 1 in Supplement 1) and more fatalities (eTable 2 in Supplement 1) when the MSEs occur. The reason for these findings could not be examined in this study; however, previous studies have shown that racial disparities exist in the care of injured trauma patients, which may partly explain why the percentage of Black population is associated with increased fatalities in MSEs . Trauma deserts, or urban communities farther than 5 miles away from trauma centers, are also more likely to be communities of color, which may contribute to this disparity .…”
Section: Discussionmentioning
confidence: 78%
“…Our lack of understanding regarding the role SCT plays in multisystem trauma is concerning, given its impact on quality of care for those in Black and Latinx communities 12. If SCT is found to be physiologically linked to multisystem trauma outcomes, then the high prevalence of SCT in communities of color in the USA may intersect with today’s concurrent epidemic of violent trauma, particularly in communities affected by legacies of structural racism, economic marginalization, and worsened by the recent COVID-19 pandemic 16. In light of our scoping literature review’s results and its clinical contexts, we have developed the following calls to action for the trauma surgery community—(1) consider testing for SCT in trauma patients that have unexpected complications, particularly VTE, rhabdomyolysis, or renal failure; (2) support research to understand how SCT impacts multisystem trauma outcomes; and (3) maintain significant caution with causal attribution of SCT to death, especially in cases of grievous bodily injury, given the current lack of medical or surgical literature to support such assertions.…”
Section: Calls To Actionmentioning
confidence: 99%
“…Given US demographics, Black Americans make up the large majority of the nation’s patient population with SCT. Accordingly, in understanding how best to consider and incorporate SCT-positive status into efforts to improve trauma outcomes, it is necessary to also reflect on how the high prevalence of SCT-positive status within Black communities may compound other known drivers of substandard trauma outcomes for Black patients—such as disparities in access to quality care at a structural, institutional, and interpersonal level 16…”
mentioning
confidence: 99%